El empleo de juegos tradicionales para potenciar la motricidad gruesa de niñas y niños de 4 a 5 años de edad de la unidad educativa municipal Héroes del Cenepa de la ciudad de Loja, periodo 2014-2015 - Veintimilla Valarezo, Angie Stefanny (2016)
This research focused on the use of traditional games to promote gross motor skills of children of 4-5 years in the Unidad Educativa Municipal Heroes del Cenepa from Loja City, 2014-2015; for that reason, the general objective was: to determine through the practice of traditional games, the strengthening of the motor skills in children 4 to 5 years from Unidad Educativa Municipal Heroes del Cenepa, during the school year 2014-2015. To carry out this research work, it was planned as a descriptive study of correlation type and among the methods used were the descriptive, analytic-synthetic-deductive and inductive quantitative; the techniques used were, the survey of teachers, psychomotor scale test to measure preschool gross motor skills of children and post-test which is the re-application of the test after the strategy to determine the progress of the children who were investigated. The developed procedures were given at the institutional level, so began asking the consent of the person who is the responsible from the school, then a work schedule for the classroom teacher while the children were motivated to do the work was delivered . The population investigated during this work were, 3 teachers and 32 children. When the investigation process started, it was determined that 16% of children surveyed had a low level of development in terms of gross motor; but after practicing traditional games, this result was reduced to 0%, in this way, the children achieved a normal level of gross motor development; which demonstrated that by following the practice of these activities children will achieve an optimal development. Therefore, it is recommended to teachers to use the game as a development strategy, because the effectiveness of this activity in the improvement of the motor skills in children is demonstrated. Finally, after making the research work and a relevant analysis about this investigation I have concluded that the game, to be considered as a basic element in the integral development of children, served as a motivating activity to strengthen important growth areas in children; and, with the practice of traditional games gross motor skills of children was strengthened, becoming visible with the results of the post-test, the effectiveness of these activities in the better development of children.